2020
DOI: 10.1186/s12920-020-0686-1
|View full text |Cite
|
Sign up to set email alerts
|

Deep learning-based cancer survival prognosis from RNA-seq data: approaches and evaluations

Abstract: Background: Recent advances in kernel-based Deep Learning models have introduced a new era in medical research. Originally designed for pattern recognition and image processing, Deep Learning models are now applied to survival prognosis of cancer patients. Specifically, Deep Learning versions of the Cox proportional hazards models are trained with transcriptomic data to predict survival outcomes in cancer patients. Methods: In this study, a broad analysis was performed on TCGA cancers using a variety of Deep L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
56
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 71 publications
(56 citation statements)
references
References 65 publications
0
56
0
Order By: Relevance
“…Multi-omics analysis of the genetic and epigenetic mechanisms was important in leukemogenesis, including abnormal gene expression, microRNA-target gene interaction network analysis, and downstream gene ontology analysis (18,36). Our study further analyzed how CLIC4 overexpression affected the prognosis in CN-AML from these aspects.…”
Section: Discussionmentioning
confidence: 94%
“…Multi-omics analysis of the genetic and epigenetic mechanisms was important in leukemogenesis, including abnormal gene expression, microRNA-target gene interaction network analysis, and downstream gene ontology analysis (18,36). Our study further analyzed how CLIC4 overexpression affected the prognosis in CN-AML from these aspects.…”
Section: Discussionmentioning
confidence: 94%
“…Unlike traditional shallow learners, deep neural networks are able to capture sophisticated, non-linear data via activation functions and multiple levels of abstraction [20] [36]. Previous studies have shown that deep learning-based survival models have superior performance compared to shallow learners such as Cox-PH and RSF [4] [11] [15].…”
Section: Deep Learningmentioning
confidence: 99%
“…Since 2018, many deep learning methods; Cox-nnet [4], DeepSurv [15], AECOX [11] and Nnet-survival [7]; have been proposed. The first three adopt the CoxPH assumption by using a Cox regression layer as its output layer, while the last one supports non-proportional hazards.…”
Section: Deep Learningmentioning
confidence: 99%
See 1 more Smart Citation
“…Huang et al developed a novel auto-encoder based model, namely AECOX, to identify prognostic marker genes from cohort transcriptomics data [14]. Comparing to classic models, AECOX utilized a novel auto-encoderbased formulation to derive non-linear features from the transcriptomics data that can well explain the low rank structure encoded in the data.…”
Section: Biomarker Predictionmentioning
confidence: 99%